Electroencephalographic accompaniment of quantitative-qualitative blood pressure clusters in patients of Truskavets’ spa - Kozyavkina, Nataliya; Vovchyna, Yuliya; Voronych-Semchenko, Nataliya; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. Earlier we studied the autonomic and endocrine accompaniments of quantitative-qualitative blood pressure (BP) clusters of profile patients of Truskavets’ spa. The purpose of this study is to clarify the electroencephalographic accompaniment in the same contingent. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP (tonometer “Omron M4-I”, Netherlands). EEG recorded a hardware-software complex “NeuroCom Standard” (KhAI Medica, Ukraine) monopolar in 16 loci. Results. The forward stepwise program identified 30 parameters as characteristic of quantitative-qualitative blood pressure clusters. In addition to BP parameters by default, 5 entropy parameters, 4 delta-rhythm, 6 theta-rhythm, 6 alpha-rhythm and 7 beta-rhythm parameters are included in the discriminant model. The most informative among them are PSD of beta-rhythm in C3 and C4 loci; alpha-rhythm in T4 and F3 loci; delta-rhythm in C3, T5 and P3 loci as well as its deviation. The accuracy of classification is 100%. Conclusion. The wide range of blood pressure - from low norm to arterial hypertension II - is accompanied by characteristic EEG conditions.